Meningkatkan Kosakata Dan Pelafalan Bahasa Inggris Siswa TK Menggunakan Metode Suggestopedia - Astari Amalia Putri; Sinta Oktaviani Safitri; Rizky Tazkiyatul Ummami; Almas Garapuri; Aditya Muhammad Akbar; Ahmadi Rahman; Alvi Siti Hanafiah; Dhimas Syamsari (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Curriculum changes are a common occurrence to test the development of a country's education level. The Kurikulum 2013 (lit. 2013 Curriculum, K-13 or Kurtilas) brings significant changes to the learning curriculum, one of which is the loss of English language learning at the elementary school (SD) level. This has led to many private Kindergarten (TK) educational institutions emphasizing English language learning in their schools to make up for the absence of English language lessons at a higher level. This is also what Aufa Saif Kindergarten, North Serpong, does. Having students with different backgrounds due to its strategic location, Kindergarten Aufa Saif Islamic School tries to unite the mindset of children from different environmental backgrounds with one lesson that can be accepted by various groups. By considering the characteristics of these partners, the community service team ran a community service activity solution for the educational aspect of English learning for kindergarten children, namely by implementing teaching and learning activities using the Suggestopedia method. We consider this method to be the most appropriate for kindergarten children because it is entertaining and does not make them bored. This method is expected to instill a sense of interest in speaking English in kindergarten children, especially in Aufa Saif Islamic School Kindergarten students as partners of this service activity. Applying positive thinking in learning English is the main focus of the community service program this time, which is adapted to current issues.